Effect of energy input on microstructure and mechanical properties in EBSM Ti6Al4V. Issue 15 (18th November 2018) - Ge, Wenjun; Lin, Feng; Guo, Chao
ABSTRACT: Electron beam selective melting technology was utilized to fabricate Ti6Al4V parts from pre-alloyed powders. Square samples of different heights were fabricated with varied fabrication parameters to understand the effect of energy input on the structures and properties. The macrostructures and microstructures were characterized by optical microscopy, scanning electron microscopy, and X-ray diffraction. The mechanical properties including microhardness and ultimate tensile strength (UTS) were investigated. The Widmanstatten structure in the top region has a slightly lower UTS but a higher microhardness than the bottom basket-weave microstructure, and the UTS in vertical orientation was lower than the horizontal orientation, which was thought to be caused by lack-of-fusion porosity defects.